Capital Structure and Corporate Control: The Effect of Antitakeover Statutes on Firm Leverage - Garvey, Gerald T.; Hanka, Gordon (Journal of Finance, 1999)
We find that firms protected by “second generation” state antitakeover laws substantially reduce their use of debt, and that unprotected firms do the reverse. This result supports recent models in which the threat of hostile takeover motivates managers to take on debt they would otherwise avoid. An implication is that legal barriers to takeovers may increase corporate slack.